Genetic diversity, antimicrobial resistance, toxin gene profiles, and toxin production ability of Bacillus cereus isolates from doenjang, a Korean fermented soybean paste. Issue 4 (12th May 2017) - Lee, Nari; Kim, Myo‐Deok; Chang, Hyun‐Joo; Choi, Sung‐Wook; Chun, Hyang Sook
Abstract: The objectives of this study were to determine the toxin gene profile, toxin production, and antibiotic resistance of Bacillus cereus isolates from doenjang, a Korean fermented soybean paste. Repetitive element sequence polymorphism‐PCR (rep‐PCR) was also used to assess the genetic diversity between these isolates. Thirty‐five B. cereus strains were isolated from 67 commercial doenjang samples, and all 35 isolates carried the nheABC and entFM genes and produced NHE enterotoxin. Of them, 12 strains harbored the emetic toxin gene ( ces ) and tested positive for the HEp‐2 cell emetic toxin assay. The B. cereus isolates were highly resistant to ß‐lactam antibiotics including ampicillin, cefepime, penicillin, and oxacillin. The rep‐PCR fingerprints of the B. cereus isolates were not influenced by the presence of toxin genes or antibiotic resistance profiles. However, rep‐PCR assay can be used to discriminate emetic B. cereus isolates from nonemetic isolates. Practical applications: Doenjang has been the focus of recent concern in Korea because of its potential to cause foodborne illness via Bacillus cereus . The results of the present study suggest that B. cereus isolates from doenjang could cause either diarrheal or emetic types of foodborne illness because all isolates contained at least one toxin and its gene, although B. cereus levels in doenjang meet the Korean Food and Drug Administration guidelines (<10 4 cfu/g). Thus, it is necessary to constantly monitor the levels of B. cereus contamination and its toxins in doenjang .